Labour law implications of the transfer of an undertaking - Smit, Nicola (University of Johannesburg, 2009)
This thesis provides a comprehensive analysis of the legal, social, and economic consequences of business transfers on employment contracts, focusing on South African law and its comparison with international standards. It critically evaluates the automatic transfer of employment contracts, the protection of employee rights, and the legal complexities surrounding insolvent undertakings.
Keywords: Labour law; Labour legislation; Transfer (Law)

Alternative means to regulate the employment relationship in the changing world of work - Vettori, Maria-Stella (University of Pretoria, 2006)
Advancing technology has caused rapid and dramatic changes in the world of work. Labour law systems grounded in the industrial era, with their emphasis on collective bargaining, are not suitable in today’s world of work. Throughout the world, the ‘atypical employee’ is replacing the standard or typical employee whose terms and conditions of employment were generally regulated by collective agreements. Atypical employee’s terms and conditions of employment generally are not regulated by collective agreements. World– wide trends in the decentralisation of collective bargaining, decollectivisation and individualisation of the employment relationship have contributed to a decline in trade union power and influence. Consequently the number of workers covered by collective agreements has decreased. Collective bargaining has been rendered less effective because of the changing the world of work. The South African labour law system places a huge emphasis on collective bargaining, particularly at industry level, for the protection of employee interests. Given these trends in the changing world of work, the appropriateness of this emphasis on industry or central level collective bargaining is questioned. The vacuum left by the inadequacy and inability of trade unions to protect employee interests in a comprehensive manner by means of collective bargaining, needs to be addressed. The following alternative means of protecting employee interests are considered: (i) The socialisation of the law of contract; (ii) the interpretation given to the constitutional right to fair labour practices; and (iii) the role of good corporate governance and corporate social responsibility. These alternative means of addressing legitimate employee interests could play a role in filling the vacuum created by trade union decline. The South African law of contract is capable of bridging the gap between law and justice by the application of the concepts of good faith and public policy, so that employment contracts may take cognisance of employee interests despite the imbalance of power between employer and employee. The protection of worker interests by means of the constitutional right to fair labour practices depends on the judge’s interpretation of what is fair. Implementation of good corporate governance codes can be influential in protecting and promoting employee interests.
Keywords: Atypical employee; CSR; Collective bargaining; Corporate Social Responsibility; Corporate governance; Decentralization; Decollectivisation; Fordism; Individualization

Theories of the company, employees and takeover regulation - Johnston, Andrew (European University Institute, 2004)
Keywords: Consolidation of corporations; European Union countries; Labor laws and legislation; Merger of corporations; Social policy

Self-employment and the personal scope of labour law : comparative lessons from France, Italy, Sweden, the United Kingdom and the United States - Engblom, Samuel (European University Institute, 2003)
The past two decades has seen a growing interest, from both policy makers and scholars, in the legal regulation of work performed by self-employed workers. Increases in non-agricultural selfemployment in industrialised countries, together with political and ideological shifts, have fuelled interest in self-employment as a means of increasing employment. The attractions of selfemployment are manifold. To firms, self-employment is part of a two-fold change in the way firms operate: the move towards more flexibility as to the size and composition of the workforce, marked by an increased use of atypical workers and the disintegration of firms by arranging production through outsourcing, subcontracting and franchising. To workers, self-employment offers the greater autonomy connected with being their own boss, a chance of higher returns, or, at least, opportunities of gainful employment in times of high unemployment. To governments, self-employment has been seen as a means of increasing the number of small businesses, supposedly beneficial to the creation of new employment. Encouraging and removing barriers to self-employment is, therefore, a priority for many governments.
Keywords: Labor laws and legislation